Sulfur substitution in a Ni(cyclam) derivative results in lower overpotential for CO2 reduction and enhanced proton reduction. Issue 18 (9th January 2019) - Gerschel, P.; Warm, K.; Farquhar, E. R.; Englert, U.; Reback, M. L.; Siegmund, D.; Ray, K.; Apfel, U.-P.
Abstract : N/S replacement in Ni-cyclam complexes highlights the importance of biologically relevant sulfur ligands in the CO2 and proton reduction. Abstract : The replacement of the opposing nitrogen atoms in 1, 4, 8, 11-tetraazacyclotetradecane (cyclam) with two sulfur atoms in 1, 8-dithia-4, 11-diazacyclotetradecane (dithiacyclam) enables the electrochemical reduction of protons and CO2 via the corresponding nickel(ii ) complex at more positive potentials. In addition, a 10-fold enhancement in the proton reduction rate of [Ni(dithiacyclam)] 2+ relative to [Ni(cylcam)] 2+ was observed. The study provides vital insight into Nature's choice of employing predominantly sulfur based ligand platforms in achieving biological proton and CO2 reductions.